2020
DOI: 10.1101/2020.11.05.369801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viscophobic turning dictates microalgae transport in viscosity gradients

Abstract: Gradients in fluid viscosity characterize microbiomes ranging from mucus layers on marine organisms and human viscera to biofilms. While such environments are widely recognized for their protective effects against pathogens and their ability to influence cell motility, the physical mechanisms controlling cell transport in viscosity gradients remain elusive, primarily due to a lack of quantitative observations. Through microfluidic experiments with a model biflagellated microalga (Chlamydomonas reinhardtii), we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…Additionally, when our analysis is extended for large viscosity gradients, the contribution of the viscosity gradient dominates the homogeneous contribution and our theory predicts accumulation of the swimmers in regions of low or high viscosity depending on the Péclet number corresponding to the transport of the stratifying agent. Stehnach (2019) observed that swimming biflagellates accumulate in the high-viscosity region for longer flagella lengths. For their experimental analysis, the length scale is , the velocity scale is and the diffusion coefficient is , which results in a Péclet number of .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when our analysis is extended for large viscosity gradients, the contribution of the viscosity gradient dominates the homogeneous contribution and our theory predicts accumulation of the swimmers in regions of low or high viscosity depending on the Péclet number corresponding to the transport of the stratifying agent. Stehnach (2019) observed that swimming biflagellates accumulate in the high-viscosity region for longer flagella lengths. For their experimental analysis, the length scale is , the velocity scale is and the diffusion coefficient is , which results in a Péclet number of .…”
Section: Resultsmentioning
confidence: 99%
“…(2018) recently suggested that the viscous torque experienced by the swimmer due to its asymmetric shape could be the cause of the preferential alignment. Stehnach (2019) showed that swimming biflagellates (wild-type Chlamydomonas reinhardtii ) have a tendency to accumulate in high-viscosity regions due to the local reduction in the swimming speed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, colloids can be exposed to almost any arbitrary external potential by using optical fields [41][42][43] and almost any kind of noise can externally be programmed by external fields [44,45]. A spacedependent friction can be imposed be a viscosity gradient in the suspending medium on the particle scale, a situation typically encountered for viscotaxis [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%